Prenatal Exposure to Respiratory Syncytial Virus Alters Postnatal Immunity and Airway Smooth Muscle Contractility during Early-Life Reinfections. - Paul M Brown; Terri J Harford; Vandana Agrawal; Belinda Yen-Lieberman; Fariba Rezaee; Giovanni Piedimonte (PLoS ONE)
Maternal viral infections can have pathological effects on the developing fetus which last long after birth. Recently, maternal-fetal transmission of respiratory syncytial virus (RSV) was shown to cause postnatal airway hyperreactivity (AHR) during primary early-life reinfection; however, the influence of prenatal exposure to RSV on offspring airway immunity and smooth muscle contractility during recurrent postnatal reinfections remains unknown. Therefore, we sought to determine whether maternal RSV infection impairs specific aspects of cell-mediated offspring immunity during early-life reinfections and the mechanisms leading to AHR. Red fluorescent protein-expressing recombinant RSV (rrRSV) was inoculated into pregnant rat dams at midterm, followed by primary and secondary postnatal rrRSV inoculations of their offspring at early-life time points. Pups and weanlings were tested for specific lower airway leukocyte populations by flow cytometry; serum cytokine/chemokine concentrations by multiplex ELISA and neurotrophins concentrations by standard ELISA; and ex vivo lower airway smooth muscle (ASM) contraction by physiological tissue bath. Pups born to RSV-infected mothers displayed elevated total CD3+ T cells largely lacking CD4+ and CD8+ surface expression after both primary and secondary postnatal rrRSV infection. Cytokine/chemokine analyses revealed reduced IFN-γ, IL-2, IL-12, IL-17A, IL-18, and TNF-α, as well as elevated nerve growth factor (NGF) expression. Prenatal exposure to RSV also increased ASM reactivity and contractility during early-life rrRSV infection compared to non-exposed controls. We conclude that maternal RSV infection can predispose offspring to postnatal lower airways dysfunction by altering immunity development, NGF signaling, and ASM contraction during early-life RSV reinfections.